Planning Alcohol Education Programs for Intercollegiate Student-Athletes - Petitpas, Albert J.; Van Raalte, Judy L. (My University, 1992)
Issues and concerns in planning and implementing alcohol education programs for student-athletes were outlined. Factors that may contribute to alcohol abuse by student-athletes were discussed, and structural and implementation problems with existing alcohol education programs were addressed. Finally, a six-part comprehensive alcohol education program was presented which includes the following components: education, enhancement, support, counseling, follow-up, and evaluation.
Keywords: drugs/alcohol